Mobile health awareness in pre-detection of mild stroke symptoms - Foong, O.-M. (Science Publications, 2014)
Stroke contributes to the third leading cause of death in Malaysia and happens to be the prime cause of disability among Malaysian. Lack of awareness and knowledge of stroke among Malaysian have often led to delay in hospital administration and reduced the chances of recovery for stroke patients. The objectives of this research are three-fold: (1) To develop a mobile application that helps to perform early detection on mild stroke symptoms (2) To increase the stroke awareness and knowledge level among the society (3) To create a reminder to constantly motivate the society to perform regular selfcheck on mild stroke symptoms. The mobile application is targeted for general public usage. Interviews were conducted with consultant neurologist and physiotherapist & rehabilitation manager of the National Stroke Association of Malaysia (NASAM). An online pre-survey has also been conducted among 70 random people to investigate the feasibility of the mobile application. The stroke predetection application was implemented in Android platform. The National Institute of Health Stroke Scale (NIHSS) will be used as a guideline for the development of self-check assessment for detecting mild stroke symptoms as it is proven to be reliable and effective evaluation technique. Empirical results show that majority of the respondents believe that the mobile stroke application can increase their stroke awareness and help them to perform early detections on mild stroke symptoms. The mobile stroke application performs satisfactorily in terms of its usefulness, usability, mobile application quality and information quality. Â© 2014 O.M. Foong et al.